ASSOCIATION OF COMPLEMENTARY AND ALTERNATIVE MEDICINE USE WITH HIGHLY ACTIVE ANTIRETROVIRAL THERAPY INITIATION - Merenstein, Daniel (2008)
OBJECTIVE: To assess whether complementary and alternative medicine (CAM) use is associated with the timing of highly active antiretroviral therapy (HAART) initiation among human immunodeficiency virus (HIV)–infected participants of the Women’s Interagency HIV Study. STUDY METHODS: Prospective cohort study between January 1996 and March 2002. Differences in the cumulative incidence of HAART initiation were compared between CAM users and non–CAM users using a logrank test. Cox regression model was used to assess associations of CAM exposures with time to HAART initiation. MAIN OUTCOME AND EXPOSURES: Study outcome was time from January 1996 to initiation of HAART. Primary exposure was use of any CAM modality before January 1996, and secondary exposures included the number and type of CAM modalities used (ingestible CAM medication, body practice, or spiritual healing) during the same period. RESULTS: One thousand thirty-four HIV-infected women contributed a total of 4987 person-visits during follow-up. At any time point, the cumulative incidence of HAART initiation among CAM users was higher than that among non–CAM users. After adjustment for potential confounders, those reporting CAM use were 1.34 times (95% confidence interval: 1.09, 1.64) more likely to initiate HAART than non–CAM users. CONCLUSION: Female CAM users initiated HAART regimens earlier than non–CAM users. Initiation of HAART is an important clinical marker, but more research is needed to elucidate the role specific CAM modalities play in HIV disease progression.